2003
DOI: 10.2337/diabetes.52.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Protein Tyrosine Phosphatase 1B Increases Insulin-Dependent Signaling in ob/ob Mice

Abstract: Protein tyrosine phosphatase 1B (PTP1B) is a negative regulator of insulin receptor (IR) signal transduction and a drug target for treatment of type 2 diabetes. Using PTP1B antisense oligonucleotides (ASOs), effects of decreased PTP1B levels on insulin signaling in diabetic ob/ob mice were examined. Insulin stimulation, prior to sacrifice, resulted in no significant activation of insulin signaling pathways in livers from ob/ob mice. However, in PTP1B ASO-treated mice, in which PTP1B protein was decreased by 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
115
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(125 citation statements)
references
References 41 publications
4
115
1
2
Order By: Relevance
“…Moreover, studies with obese rats have shown that expression of leucocyte common antigen-related protein tyrosine phosphatase in liver is downregulated after TNFα blockade [41], and in rat hepatoma cells TNFα increased SHIP2 production. Overactivation of phosphatases is one way in which insulin signalling becomes blocked, and PTPN1, which dephosphorylates the activated insulin receptors and their substrates, has been shown to play a major role in both insulin resistance and type 2 diabetes [42,43]. We therefore decided to check whether lack of PTPN1 in brown adipocytes might confer protection against TNFα-induced insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies with obese rats have shown that expression of leucocyte common antigen-related protein tyrosine phosphatase in liver is downregulated after TNFα blockade [41], and in rat hepatoma cells TNFα increased SHIP2 production. Overactivation of phosphatases is one way in which insulin signalling becomes blocked, and PTPN1, which dephosphorylates the activated insulin receptors and their substrates, has been shown to play a major role in both insulin resistance and type 2 diabetes [42,43]. We therefore decided to check whether lack of PTPN1 in brown adipocytes might confer protection against TNFα-induced insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The role of GSK-3β as a potential drug target has become more and more prominent in the last years (Phukan et al 2010). Several studies reported that inhibition of GSK-3β by selective small molecules is protective in clinically relevant disease models: GSK-3β inhibition was shown to improve insulin resistance in type II diabetes (Gum et al 2003;Ring et al 2003), to have beneficial effects in neurological disorders like Alzheimer's disease (Hsiung et al 2003) and to reduce cardiac hypertrophy and ischaemia (Morisco et al 2001). Despite increasing evidence for the therapeutic potential of GSK-3β inhibition to counteract various cytotoxic stressors, to our knowledge, there are no studies investigating GSK-3β inhibition in the model of experimental PD.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy is probably attributable to estrogen action depending on intracellular machinery that differs among various cell types [26,27]. PTP1B is an important protein phosphatase that is known to regulate IRS-1 tyrosine phosphorylation [28][29][30]. We also examined PTP1B expression, but it did not change after E2 treatments.…”
Section: Discussionmentioning
confidence: 99%